A mathematical model for mosquito infestation - López C., Roxana (2019)
We propose and analyze a mathematical model in ordinary differential equations to describe the dynamics of mosquitoes infested by bacteria. The introduction of some bacteria in mosquitoes population aims to diminish gradually the transmission of vector host-diseases. This is a good strategy of biological control.